A structure of support to address the socio-emotional needs of high school learners: a case study of one government high school in Johannesburg - Brand, Emma J (My University, 2016)
South African youth face a variety of challenges and barriers to learning. The prevalence of learners with emotional and behavioural barriers to learning (EBD) in South African schools is significantly increased due to the disadvantaged circumstances that many of the learners live in. Education White Paper 6 states that educational structures of support should be established to provide support to these learners. These structures of support include; the school based support team (SBST), educators, the principal, the school management team (SMT), educational psychologists, the school governing body (SGB), families, communities, professionals such as health care workers, social workers and non-profit organisations (NGOs). This research is a qualitative inquiry that provides a case study of one government high school in Gauteng with the primary aim of examining the structure of support available to address the socio-emotional needs of high school learners. There is limited information on the role of Life Orientation educators within this structure of support. Thus the research examines what role Life Orientation educators could play when working collaboratively to provide socio-emotional support to high school learners. The following data collection methods were used; semi-structured interviews, focus group interviews, observation and document review. Through the process of content analysis and through an acquisition of an interpretivist lens, the research gained a deep understanding of the lived experiences of the participants, relying on their perceptions and interpretations thereof. It was found through the examination of the research findings that there is a need for more educational psychologists positioned at the school level and district education levels.
A research report submitted to the Department of Psychology, Faculty of Humanities, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Education (Educational Psychology) Johannesburg, South Africa February 2014
Keywords: Learning, Psychology of; High school facilities - -Planning.